Przekład jako akt subwersji, czyli o pewnym polskim tłumaczeniu tragedii historycznej Theodora Körnera pt. Zriny - Małczak, Leszek (Przekłady Literatur Słowiańskich, 2018)
Translation as an Act of Subversion: About one of the Polish Translations of Historical Tragedy Zriny by Theodor Körner The object of the analysis in this article is one of the Polish translations of historical tragedy of Theodor Körner entitled Zriny. The German author’s piece has been at least six times translated into Polish language and was — especially in the second part of the 19th century, after the collapse of January Uprising — very popular. The reason of the popularity was his subversion. Through Zriny it was possible to talk about a struggle for freedom — the theme forbidden by Russian censorship. Historical piece written by a foreign author, which talks about the struggle for freedom and for defence of the homeland, the struggle lead by someone else, in other time and place, became a medium for manifesting of patriotic feelings. This function of Polish Zriny confirms his interpretation in critics and one of the translations which was written by Ludwik Jenike in Russian occupation zone with all subversive translation shifts made by the translator. KEY WORDS: subversion, Theodor Körner, Ludwik Jenike, translation, patriotism